The world economic crisis as a changed circumstance - Hermann Ferré; Kabir Duggal (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
In September 2008, the bankruptcy of Lehman Brothers sent financial markets in the United States into a spin. Credit markets froze as banks began to mistrust counterparties, not knowing the extent of toxic assets in loan portfolios that could lead to another major bank collapse. The crisis quickly spread around the world. Governments were urged to take drastic measures. Experts discussed the possible nationalization of portions of the U.S. banking industry and other sectors. Other countries also considered measures to save key industries.
Keywords: 330